# Homework Help

eNotes Homework Help is a way for educators to help students understand their school work. Our experts are here to answer your toughest academic questions! Once it’s posted to our site, your question could help thousands of other students.

### Showing All Questions Unanswered Answered Popular Recommended in All Subjects Literature History Science Math Arts Business Social Sciences Law and Politics Health Religion Other

• Math
Given: `y=2x^3+6x^2-1` `` The derivative is: `y'=6x^2+12x`

Asked by enotes on via web

• Math
Given: `y=(pi)/(2)sin(theta)-cos(theta)` The derivative is: `y'=(pi)/(2)cos(theta)+sin(theta)` ``

Asked by enotes on via web

• Math
Given: `g(t)=picos(t)` Find the derivative using the product rule: `d/dx[f(x)g(x)]=f(x)g'(x)+g(x)f'(x)` The derivative is: `g'(t)=pi(-sin(t))+cos(t)(0)` ` g'(t)=-pisin(t)` ``

Asked by enotes on via web

• Math
Given: `y=x^2-(1)/(2)cos(x)` The derivative is: `y'=2x+(1)/(2)sin(x)` ``

Asked by enotes on via web

• Math
Given: `y=7+sin(x)` The derivative is: `y'=cos(x)` ``

Asked by enotes on via web

• Math
Rewrite the `1/x` term as a fraction. `y= x^-1 -3sin(x)` Take the derivative of the first term using the power rule. `y'=-x^-2 -3cos(x)` Simplify and eliminate the negative exponent. The answer...

Asked by enotes on via web

• Math
Given: `y=(5)/(2x)^3+2cos(x)` `` Simplify the given. `y=(5)/(8x^3)+2cos(x)` `y=(5x^-3)/(8)+2cos(x)` Find the derivative. `y'=(-15x^-4)/(8)-2sin(x)` `y'=(-15)/(8x^4)-2sin(x)`

Asked by enotes on via web

• Math
Rewrite the function so that we can use the power rule to take the derivative. `f(x)= 8x^-2` Take the derivative. `f'(x)= -2(8) x^-3` `f'(x)= -16/x^3` Substitute the given x value from the...

Asked by enotes on via web

• Math
Rewrite the given function so that we can proceed with the power rule instead of the quotient rule. `f(t)=2-4t^(-1)` Take the derivative of the given function. The derivative of a constant is...

Asked by enotes on via web

• Math
Take the derivative for the derivative function. `f'(x)= 21/5 x^2` Substitute the point where x=0 to find the slope at that point. `f'(x)= 21/5 (0)^2= 0` The slope at that point is zero....

Asked by enotes on via web

• Math
Take the derivative of the function. `y' = 8x^3` Substitute the x value of the given point. `y'(1) = 8(1)^3 = 8` The derivative, or slope, at point (1,-1) is eight. Check by graphing the...

Asked by enotes on via web

• Math
Use the power rule and the chain rule to find the derivative. `y' = 2(4x+1) * (4)` `y'=8(4x+1)` `y'=32x+8` Substitute the value at x=0 from the given point. `y'=32(0)+8= 8` The slope at the...

Asked by enotes on via web

• Math
Take the derivative of the given function. The chain rule will be shown in the steps. The derivative of the inner function (x-4) with the respect to x is 1. `f'(x) =2 * 2(x-4)^(2-1) * (1)`...

Asked by enotes on via web

• Math
Take the derivative. Be careful that the derivative of theta with respect to theta is one! `f'(theta)= 4cos(theta)-1` Substitute the point given to determine the derivative: ` ` `4cos(0)-1=...

Asked by enotes on via web

• Math
Given: `y=12` The derivative of a constant will always be zero: The derivative is: `y'=0` ``

Asked by enotes on via web

• Math
Given: `f(x)=-9` The derivative of a constant will always be zero. The derivative is: `f'(x)=0` ``

Asked by enotes on via web

• Math
Given: `y=x^7` The derivative is: `y'=7x^6` ``

Asked by enotes on via web

• Math
Given: `y=x^(12)` The derivative is: `y'=12x^11` ``

Asked by enotes on via web

• Math
This function is the same as: `y= x^-5` Use the power rule. `d/dx x^n = nx^(n-1)` `y'=-5x^(-6)` The answer is: `y=-5/x^6`

Asked by enotes on via web

• Math
Given: `y=(3)/(x^7)` The given is equivalent to: `y=3x^(-7)` Find the derivative: `y'=-21x^(-8)` Simplify the derivative: `y'=(-21)/(x^8)` ``

Asked by enotes on via web

• Math
Rewrite the function: `y=x^(1/5)` Use the power rule. `y'=1/5 x^(1/5-1) = 1/5 x^ (-4/5) ` The answer is: `y=1/(5x^(4/5))`

Asked by enotes on via web

• Math
The square root of a function can be rewritten as a fraction. `g(x)= x^(1/4)` Use the power rule. `g'(x)= 1/4 x^ (1/4-1)= 1/4 x^(-3/4)` Rewrite the answer to eliminate the negative exponent. The...

Asked by enotes on via web

• Math
Given: `f(x)=x+11` The derivative is: `f'(x)=1` ``

Asked by enotes on via web

• Math
Given: g(x)=6x+3 g'(x)=6 The derivative is: 6

Asked by enotes on via web

• Math
So we know that a bobbin has an inside wheel that has a diameter of 5 cm and an outer wheel with a diameter of 10 cm. In order to determine how far the end of the thread has moved, we have to...

Asked by user6243922 on via web

• Math
Denote the function under integral as a(t) and its antiderivative as A(t): `a(t) = 3sqrt(t)` , `A'(t) = a(t)` Then `F(x) = A(sin(x)) - A(0)` and therefore `F'(x) = A'(sin(x))*[sin(x)]' =...

Asked by vrwarrier on via web

• Math
Find the nth term of the quadratic sequences The formulae for quadratic sequences are established by taking second differences between the list of terms. If the sequence is indeed quadratic (of...

Asked by abb3y-15 on via web

• Math
To generate terms in a sequence, you would put in the number 1, 2, 3, 4, 5, . . ., etc., for however many terms you are looking for. For instance, to generate the first terms in each sequence, you...

Asked by abb3y-15 on via web

• Math
The definite integral `int_0^1 dx/(1+sqrt x)^4` has to be determined. This can be done using substitution. Start with the indefinite integral `int dx/(1+sqrt x)^4` Let `1 + sqrt x = y` `dy/dx =...

Asked by tonys538 on via web

• Math
The definite integral `int_a^5 x^2+4x+1 dx = 132` . The value of a needs to be determined. `int_a^5 x^2 + 4x + 1 dx` = `int_a^5 x^2 dx+ int_a^5 4x dx+ int_a^5 1 dx ` = `[x^3/3]_a^5 + [4x^2/2]_a^5...

Asked by tonys538 on via web

• Math
The integral `int (x^2+1)(x^3+3x)^4 dx` has to be determined. Using substitution is the simplest way to arrive at the result. Let `y = x^3+3x` Taking the derivative of both the sides `dy/dx =...

Asked by tonys538 on via web

• Math
It is not clear from the question if it is n2 or n^2. I am assuming it is n^2. Bronze series: first 5 terms n2 + 1: take n = 1, we get 2. Similarly for n= 2,3,4,5; we get 5,10,17,26. Similarly, for...

Asked by abb3y-15 on via web

• Math
If you are asking how to tell if an answer is viable; a viable answer, means that our result is a possible solution to the question being asked. After solving a question or an equation in...

Asked by enotes on via web

• Math
The diameter is an important parameter of a circumference. Geometrically, the diameter is defined as a secant line to the circumference that passes through its center. Another important parameter...

Asked by enotes on via web

• Math
If you are given a fraction you can find an equivalent fraction by multiplying the numerator and denominator by the same number. Example 1: If you are given the fraction 1/2. You can multiply the...

Asked by enotes on via web

• Math
A mixed number consists of an integer part and a fraction. In fact the mixed number can be seen as the sum of the integer part plus the fractional part. For example, the mixed number 3 (1/5), can...

Asked by enotes on via web

• Math
Another way to show that `lim_(x->0) sinx/x = 1` is by using the L'Hospital rule. According to this rule, `lim f(x)/g(x) = lim (f'(x))/(g'(x))` . That is, the limit of the ratios of functions...

Asked by aaaaaaaaaaaa on via web

• Math
Because the variable is raised to a variable power, you need to apply the natural logarithm both sides, such that: `ln y = ln (x^(sin x))` Using the property of logarithms, yields: `ln y = sin x*ln...

Asked by enotes on via web

• Math
Differentiate ` y=sqrt(x)^x ` : Rewrite the right hand side: `y=x^(x/2) ` (Note that `sqrt(x)=x^(1/2) ` so `sqrt(x)^x=(x^(1/2))^x=x^(x/2) ` ) Take the natural logarithm of both sides:...

Asked by enotes on via web

• Math
Differentiate `y=(cos(x))^x ` : Take the natural logarithm of both sides: `lny=ln(cos(x))^x ` Use the power property of logarithms: `lny=xln(cos(x)) ` Differentiate; use the product rule on the...

Asked by enotes on via web

• Math
given `y = (sinx)^(lnx)` taking log to the base 'e' both sides we get, `lny = lnx*(lnsinx)` Differentiating both sides we get `(1/y)*dy/dx = (1/x)*{lnsinx} + (cosx/sinx)*lnx` or, `y*dy/dx...

Asked by enotes on via web

• Math
`y = (tanx)^(1/x)` taking log to the base 'e' both sides we get lny = (1/x)*tanx differentiating both sides we get (1/y)*dy/dx = `[(1/x)*sec^2x] + [-(1/x^2)*tanx]` `or, dy/dx = y*[{(1/x)*sec^2x} -...

Asked by enotes on via web

• Math
given: `y = (lnx)^cosx` taking log both sides we get `lny = cosx*{ln(lnx)}` Differentiating both sides we get `(1/y)*dy/dx = -sinx*{ln(lnx)} + {cosx/(x*lnx)}` `or, dy/dx = y*[-sinx*{ln(lnx)} +...

Asked by enotes on via web

• Math
`y = ln{(e^-x) + x*(e^-x)}` taking antilog both sides we get `e^y = (e^-x) + x*(e^-x)` differentiating both sides `(e^y)dy/dx = -(e^-x) -x*(e^-x) + (e^-x)` `dy/dx = (e^-y)*[-x*(e^-x)]` `or, dy/dx =...

Asked by enotes on via web

• Math
We have H(z)=ln(sqrt((a^2+z^2)/(a^2-z^2))). We will do the differentiation in steps, using the chain rule. Suppose you have H(z)=f(g(u(z))). Then H'(z)=f'(g(u(z)))*g'(u(z))*u'(z). In our case f is...

Asked by enotes on via web

• Math
Given `y=2*x*log10(sqrt(x))` we wish to find y'(x). Write y into separate functions as follows: let `f(x)=2*x, g(x)=log10(x), w(x)=sqrt(x).` Use the Chain rule: `d/dx F(G(x))= F'(G(x)) * G'(x)` and...

Asked by enotes on via web

• Math
We are given y=log2(exp(-x)*cos(pi*x))=1/ln(2)*ln(exp(-x)*cos(pi*x)). Since the domain of ln(X) is X>0, it means cos(pi*x) cannot equal to zero, we will use this later. First we use the Chain...

Asked by enotes on via web

• Math
Find y' and y''. For the first derivative, use the product rule AB'+BA'. Be warned that since we have a ln(2x) term, we will need to use chain rule, which is the derivative of the inner term...

Asked by enotes on via web

• Math
You need to find the first derivative of the function, using the quotient rule, such that: `y' = ((ln x)'*x^2 - ln x*(x^2)')/((x^2)^2)` `y' = (x^2/x - 2x*lnx)/(x^4)` `y' = (x - 2x*lnx)/(x^4)` You...

Asked by enotes on via web